SIGRA - Sistema integrado de gestão de riscos ambientais: modelo conceitual - Patrocínio, Jose Eduardo Modesto do (2002)
The SIGRA Project has the object of changing paradigms trough the visualization of actions. This is one of the principies of the management for information and knowledge. Due to this, the SIGRA is supposed to be a tool of systematic, integrated and dynamic approach with easy accessibility via Internet, sharing the management, a tool that seeks for market niches characterized by interpreunners that already have integrated management but have problems wjth the system in use, or those that are on the beginning and intermediate levei of certification.